Impact of extreme physical exercise on human body - Jakl, Martin; Skořepa, Pavel; Horáček, Jan (Vojenské zdravotnické listy, 2016)
Extreme physical exercise is potentially harmful or even lethal activity. It is associated with several compensatory mechanisms focused on increasing functional capacity. Hormonal and metabolic pathways rearrange to maintain glucose supply in working tissue. Cardiovascular system substantially increases cardiac output and redistributes blood flow in working muscles. Respiratory system increases tidal volume and respiratory rate. Immune system and other systems are also affected. If capacity of these mechanisms is exceeded, organism can be severely damaged. Frequently observed disturbances include hypoglycemia, mineral level disorders, bronchoconstriction, immune system impairment etc. More severe disturbances include arrhythmias, myocardial stunning, hypoxemia, rhabdomyolysis and many others. Early diagnosis and treatment of these disturbances is essential for minimizing the health impairment. Unfortunately, in military settings are diagnostic and therapeutic options often limited. Moreover, physiological or benign processes can mimic life threatening conditions. Without complex understanding of participating pathophysiological mechanisms and interpretation of clinical findings might be confusing and treatment inefficient or even deleterious.
Keywords: Rhabdomyolysis; Physical Exertion; kosterní svaly; zánět; osteoartróza; svalová únava; Cardiovascular Physiological Phenomena; energetický metabolismus; lidé; Energy Metabolism; kardiovaskulární fyziologické jevy; Muscle, Skeletal; Respiratory Insufficiency; Cardiorespiratory Fitness; Inflammation; rhabdomyolýza; Muscle Fatigue; kardiorespirační zdatnost; tělesná námaha; Osteoarthritis; respirační insuficience; Humans